Effects of Dubai quality awards criteria on customer growth: an empirical investigation in the UAE - Hawarna, Shatha; Osman-Gani, AAhad M. (Hamdan Bin Mohammed Smart University, 2017)
Purpose: This paper presents the findings of an empirical research on the effects of Dubai Quality Award on customer growth. Despite some research was done on Quality Awards, no prior study has measured the effects of the Dubai Quality Award (DQA) by considering each of the criterion as the antecedents of effects on customer growth in the UAE. Design/Methodology/Approach: A quantitative research design is selected given its appropriateness toward achieving the study objectives. The target population was the organisations that won DQA using the EFQM framework during the period of 2001 to 2011 (which meets the requirements of three years after winning the award). A total of 51 organisations was identified using the criteria established for the research. The accessible population with usable responses for this study was 45 DQA winning organisations. Findings: This study found statistically significant positive relationship between the DQA criteria and Customer growth. Recommendations based on the research findings were also provided for professional practice and for future research. Originality/Value: The results of this empirical study contributed to quality management theory with the conclusions derived from the findings that statistically significant positive relationships exist between the DQA criteria and customer growth.